Isolated Cortical Vein Thrombosis: A Case Report - Olla Ibrahim; Enas Alhaen; Walid Mohmmad (AlQalam Journal of Medical and Applied Sciences, 2024)
Isolated cortical vein thrombosis (ICVT) is a rare entity of cerebral venous thrombosis (CVT) that represents a third leading cause of death during pregnancy and puerperium. IVCT manifests with wide spectrum of symptoms including headache, seizure, focal neurological deficits and changed mental status, makes the diagnosis challenging. Pregnancy, puerperium, lumbar puncture, trauma and infection, genetic predisposing and acquired prothrombotic causes, all are well recognized risk factors for ICVT. Although no established universal consensus for management, IVCT generally treated by anticoagulant. In this paper, a case of IVCT reported in 25 years old postpartum mother, delivered by cesarean using epidural anesthesia. The case presents by persisting non-orthostatic headache in first few days post-delivery that treated as post dural puncture headache but not improved. On day 7 post-delivery developed multiple episodes of focal convulsion progressed to generalized tonic-clonic convulsion associated by left hemi-paresis. MRI gradient echo sequences showed liner hypo-signal lesion with configuration of cortical vein over right high parietal area. The MRV showed multiple small filling defects along the right cortical vein in favor IVCT. The patient treated successfully by enoxaparin (according her body weight) followed by warfarin for 3 months with complete resolution of the neurological deficit. تخثر الوريد القشري المعزول نوع نادر من التخثر الوريدي المخي الذي يمثل السبب الثالث للموت خلال الحمل والنفاس. هناك مجموعة واسعة من الأعراض التي تأتي مع تخثر الوريد القشري المعزول مثل الصداع و نوبات تشنج والعجز العصبي البؤري وتغير الحالة العقلية وهذا يجعل التشخيص صعبا. الحمل و النفاس والبزل القطني والرضوح والعدوى والعوامل الوراثية وأسباب تجلط الدم المكتسبة كلها عوامل خطر معروفة جيدا لتخثر الوريد القشري المعزول ,على الرغم من عدم وجود إجماع على طريقة العلاج , تخثر الوريد القشري المعزول عادة يعالج بمضادات التخثر. في هذه الورقة سجلت حالة لتخثر الوريد القشري المعزول لسيدة تبلغ من العمر 25 سنة بعد الولادة والولادة كانت بالعملية القيصرية باستخدام ا لتخدير فوق الجافية , الأعراض التي كانت تعاني منها الحالة صداع غير انتصابي مستمر في الأيام الأولى بعد الولادة والذي تم علاجه على انه صداع ما بعد ثقب الجافية ولكن لم يتحسن . في اليوم السابع بعد الولادة تطورت الأعراض إلى نوبات متعددة من التشنج البؤري ثم إلى تشنج منشط رمعي معمم مصاحب له خزل شقي في الجهة اليسرى. أظهرت تسلسلات صدى التدرج في التصوير بالرنين المغناطيسي آفة نقص إشارة البطانة مع تكوين الوريد القشري فوق المنطقة الجدارية العليا اليمنى كما اظهر تصوير الأوردة بالرنين المغناطيسي عيوبا صغيرة متعددة في الحشوة على طول الوريد القشري الأيمن يتماشى مع تشخيص التخثر الوريد القشري المعزول . تم علاج المريضة بنجاح بواسطة الاينوكسابارين (حسب وزن جسمها) ثم بالورفارين لمدة 3 أشهر مع تعافي تام من العجز العصبي.